2020
DOI: 10.1101/2020.09.07.286831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-molecule FRET monitors CLC transporter conformation and subunit independence

Abstract: CLC transporters catalyze the exchange of chloride ions for protons across cellular membranes. As secondary active transporters, CLCs must alternately allow ion permeation to the extracellular and intracellular sides of the membrane, adopting outward-facing and inward-facing conformational states. Here, we use single-molecule Forster resonance energy transfer (smFRET) to monitor the conformational state of CLC-ec1, an E. coli homolog for which high-resolution structures of occluded and outward-facing states ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 72 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…[90][91][92][93][94][95][96] The impact of mutations on function can be monitored by ATPase assays [79,90,[97][98][99][100][101] or transport assays. [78,90,[105][106][107][108]93,94,96,97,100,[102][103][104] In transport assays, the protein is either overexpressed in a cell or incorporated into liposomes and the accumulation of fluorescent [78,97,105] or radiolabeled substrate [90,93,94,96,100,102,103,[106][107][108] in the compartment (cell or vesicle) is measured. Good examples for such careful controls are LmrP transporter variants whose activities were checked with the fluorescent ligand Hoechst, [105] or variants of the Glt Ph transporter in liposomes where the uptake of the radioactive substrate [ 3 H]-Asp was used to confirm activity.…”
Section: Specific Labeling and Functionalitymentioning
confidence: 99%
See 4 more Smart Citations
“…[90][91][92][93][94][95][96] The impact of mutations on function can be monitored by ATPase assays [79,90,[97][98][99][100][101] or transport assays. [78,90,[105][106][107][108]93,94,96,97,100,[102][103][104] In transport assays, the protein is either overexpressed in a cell or incorporated into liposomes and the accumulation of fluorescent [78,97,105] or radiolabeled substrate [90,93,94,96,100,102,103,[106][107][108] in the compartment (cell or vesicle) is measured. Good examples for such careful controls are LmrP transporter variants whose activities were checked with the fluorescent ligand Hoechst, [105] or variants of the Glt Ph transporter in liposomes where the uptake of the radioactive substrate [ 3 H]-Asp was used to confirm activity.…”
Section: Specific Labeling and Functionalitymentioning
confidence: 99%
“…[121] Thus numerous smFRET studies have been performed using detergents [121][122][123] and provided important insights. [78,79,108,[91][92][93][94]99,102,104,105] Yet, studies of transporters in membrane environments, which better mimic native conditions, showed that lipids play important roles in maintaining their structural and functional integrity. [120,[124][125][126][127][128] For certain transporters such as Glt Ph , dynamics in micelles do not differ significantly from those found in a lipid bilayer.…”
Section: Membrane Mimicking Environmentmentioning
confidence: 99%
See 3 more Smart Citations